Обзор принципа работы триангуляционного датчика - Рогач, О. О.; Мясоедов, В. Г. (ХНУРЕ, 2019)
The triangulation control method is based on the calculation of the desired distance through triangle relations using known system parameters. It allows you to measure both the relative change in the distance from the sensor to the object being monitored and its absolute value. Moreover, the controlled distance can have a scale from several micrometers (for example, when monitoring the surface of microelectronic crystals) to hundreds and thousands of meters (for geodetic applications).